Optical materials for flexible and stretchable random lasers - Gomes, Anderson S.L.; Valente, Denise; de Oliveira, Helinando P.; Ribeiro, Sidney J.L. [UNESP]; de Araújo, Cid B. (Elsevier, 2022)
The development of photonic devices has been largely benefitted by the offer of new flexible and stretchable materials. Many innovative components and devices have been developed for light-based applications. Presently it is recognized that integration of active and passive elements on flexible substrates will simplify many proposed photonic applications. For example, extensive variety of optical sensors integrated on biological tissues, optical waveguides based on polymer films, flexible organic interconnects, and imaging devices, are receiving large attention nowadays. Especially, the search for optical sources such as organic light emitting diodes and lasers are two booming areas. Flexible Random Lasers (FRLs) based on stretchable materials, in particular, have been object of intense research in the past few years. In this paper we present an overview of the FRLs literature, with emphasis in 2D and 3D materials, and the achievements and availability of new flexible organic and inorganic materials for FRLs. In Section 2 we present some basic ideas of Random Lasers (fundamentals, operation, and physical characteristics). Section 3 contains a detailed assessment of various types of FRLs based on biopolymers, electrospinning and natural fibers, silicones, semiconductor nanowires, perovskites, chiral molecules, polyethylene and polystyrene substrates. In Section 4 we present our perspective on new opportunities and emerging applications in this field.
Keywords: Flexible optical materials; Flexible photonics; Flexible random lasers; Random lasers